The Influence of Transformational Leadership and Work Motivation on Employee Performance: Case Study in One of The Official Companies in The City of Bandung - Ika Safitri; Adhie Fasha Nurhadian (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
This study aimed to determine the effect of transformational leadership and work motivation on employee performance at one of the Bandung City service offices by obtaining accurate data and collecting the necessary data for analysis. This study aimed to determine the influence of transformational leadership and work motivation on employee performance in the City of Bandung. This study used descriptive methods and verified analysis with 35 employees (census) at the Bandung City Office, with the results of this study using correlation analysis, path analysis, and coefficient of determination analysis. Based on the research carried out at the Bandung City Office, transformational leadership gets quite good results, work motivation gets pretty good results, and performance gets pretty good results. The correlation between transformational leadership and work motivation yields a positive relationship of 0.709. The coefficient of determination is 71.4%. Therefore, the direct and indirect influence of transformational leadership on employee performance is 0.398. The direct and indirect influence of work motivation on employee performance is 0.316, so the total effect is 0.714 or 71.4%. The remaining 28.6% is a variable that also influences performance in official offices in Bandung but has yet to be studied.